Families coming together in prison: An examination of visitation encounters. (October 2016) - Tasca, Melinda; Mulvey, Philip; Rodriguez, Nancy
Despite great strides in research on the collateral consequences of incarceration, we know relatively little about family life during imprisonment. In an effort to extend prior work, the current study examines family processes among caregivers, prisoners, and children during prison visitation. Drawing from in-depth interviews with 52 caregivers of children of incarcerated parents, we use open and axial coding techniques to identify the interactions and interpersonal exchanges that take place among family members during prison visitation. Analyses revealed that in addition to universal engagement in Family Time, three familial processes unfolded in the carceral setting: Attempts to Bond, Declarations of Family Responsibilities, and Messages of Reform . Our findings illuminate the complex needs and fragile relationships of prisoners and their families, and have important implications for reentry, offender rehabilitation, and family well-being.